Debatable points of using angiotensin-converting enzyme inhibitors and angiotensin receptor antagonists in patients with COVID-19 - O. M. Drapkina; L. E. Vasilyeva (Кардиоваскулярная терапия и профилактика)
The COVID-19 pandemic is a serious threat to global health. The infection mechanism is the binding of SARS-CoV-2 to angiotensin-converting enzyme 2 (ACE2) and internalization of the complex by the host cell. ACE inhibitors/angiotensin receptor antagonists (ARA) are known to increase ACE2 expression and are recommended for the treatment of many cardiovascular diseases (CVD). Thus, it has been suggested that treatment with renin-angiotensin-aldosterone system blockers (RAAS) increases the viral load and the risk of severe acute respiratory distress syndrome. However, ACE2 also converts angiotensin II into substances with cardioprotective effects. In addition, there is no evidence that RAAS inhibitors increase the severity of COVID-19 infection, while the risks of withdrawal of ACE inhibitors/ARA in patients with CVD are proven. There is also no evidence to support the idea that the administration of ACE inhibitors/ARA promotes the coronavirus’s penetration by increasing the ACE2 expression. According to the guidelines of the Russian Society of Cardiology and the consensus statements of international cardiology societies, it is necessary to continue taking RAAS inhibitors in high-risk patients with COVID-19. This review provides an analysis of foreign articles revealing the pathophysiological pathways and recommendations for using ACE inhibitors/ARA in patients with CVD and COVID-19 infection.